Time spent cycling is the most predictive factor in order to be successful in a off-road triathlon race - Caria. A.; Massidda, M. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Race result prediction is one of the most interesting aspects for sports scientists. Triathlon is a 3-event endurance sport (swimming, cycling and running) that are generally completed in succession and are separated each other by a transition periods of only a few seconds (Suriano et al., 2010). A scarce number of studies have examined the Triathlon in its entirety, particularly as far as the relationships between overall and single event competition times and positioning during an official off-road race. Purpose The purpose of this study was to identify the most important event in order to be successful in a off-road Triathlon race. Methods: Two-hundred-ninetyseven athletes were studied (n=260 males, n=37 females) during a world stage of the `X TERRA World Championship`. All athletes have completed the World`s off-road Triathlon race (1.5 km, 30 km, 10 km) . The Swim Time (S), the Bike Time (B), the Run Time (R), the Transition Time between S and T (T1) and Transition Time between the T and R (T2) were recorded for each athlete using the SYNOPSIS GPS system (T4 model). The analysis was computed for each gender separately, considering the final standings as dependents variables and the S, B, R, T1 and the T2 as independent variables. Results: For males, the 99.4% of the final standings variability was explained by the B (R2adj=.9940, F=43098.82, df=1, p<0.01). The second most important variable (even if with a less significant level with respect to B) was the R (R2adj=.9943, F=22777.01, df=2, p<0.01), followed by the T2 (R2adj=.9945, F=15652.47, df=3, p<0.01) and by the T1 (R2adj=.9946, F=11971.65, df=4, p<0.01). For females, the only significant variable entered in the regression equation in predicting the variability of the final standing was the B (R2adj= .9951, F=7259.37, df=1, p< 0.01). Discussion: Our results suggest that the time spent cycling during off-road Triathlon competition was the best predictor of the final positioning in both sex. However, the time spent running and the transition times were correlated to the final standing in males but not in females. Finally, swimming time was not significantly related to the final positioning in both gender. This result agrees with those of previous researches on Triple Iron Triathlon (11.6 km swimming, 540 km cycling and 126.6 km running) that showed the low importance of swimming performance in order to be successful during competition (Knechtle and Kohler, 2009). In conclusion, Triathlon is more than the sum of its parts, but it is "one sport, three disciplines and two transitions" (Millet and Vleck, 2000).